The Growth of Hard Coral (Acropora sp.) Transplants in Coral Reef of Malalayang Waters, North Sulawesi, Indonesia - Alex D. Kambey (Sam Ratulangi University, 2013)
Main coral reef building components, Scleractinian corals, has the highest distribution in Indonesia, at least 590 species known of 793 species in the world. Studies on damaged coral community transplantation have been done to observe their growth and adaptation ability. A four-month observation found that average length increment at 9 M deep was linearly 0.375 cm, 0.632 cm, and 0.732 cm at the first, second, and third month, respectively, at 6 M deep, it was 0.455 cm, 0.689 cm, and 1.012 cm, at the first, second and third month, respectively, and at Â 3 M deep, it was 0.55 cm, 1.05 cm and 1.1, at the first, second, and thrid month, respectively. Mean relative length increment at 9 M deep occurred every month as much as 4.25%, 8.23%, and 9.86% at the first, second, and third month, respectively. Similarly, it occurred in 6 M deep, 4.12%, 9.14%, and 11.28% at the first, second, and third month, respectively. However, at 3 M deep, it occurred only at the first and second month, 7.33% and 12.73%, while it declined at the third month, 11.7%. Keywords : Ecosystems, Coral Reef, Scleractinia, Malalayang, Manado